Characterization of the symptoms of Thanatephorus sp. in potato (Solanum tuberosum) - Aguilar-Zamora, María Cecilia (2026)
Introduction. Thanatephorus sp. is a basidiomycete, with high genetic variability and a broad host range, capable of forming survival structures. Objective. To characterize the symptomatology caused by the phytopathogen Thanatephorus sp. in potato (Solanum tuberosum) crops. Materials and methods. The study was conducted from June to December 2023 at the Plant Pathology Laboratory of the Universidad de Costa Rica, Sede del Atlántico, Turrialba, Costa Rica. Vegetative and reproductive plant tissues were collected from potato plants showing symptoms associated with Thanatephorus sp. The isolates were purified, and the pathogen was cultured on artificial media. The fungus was further purified and inoculated into soil, and applied via foliar spraying to potato plants in order to observe disease symptom development. Leaves, stems, and other plant parts exhibiting abnormal lesions were evaluated. Results. Thanatephorus sp. was primarily isolated from the foliage of potato plants and successfully grew in vitro on PDA (potato dextrose agar). The fungus exhibited branched morphology consistent with basidiomycetes and formed sexual reproductive structures, including basidiospores. Hyphal fusion (anastomosis) was observed, contributing to increased genetic variability of the pathogen. Symptom development began with small necrotic lesions on the leaf blade, surrounded by chlorotic halos; these lesions coalesced, leading to complete foliar tissue necrosis. Lesions were also observed on different plant organs. Survival structures (sclerotia) produced by Thanatephorus sp. were identified. Conclusions. The phytopathogen Thanatephorus sp. causes damage to leaves, stems, and tubers, and produces survival structures that facilitate its dissemination. Its symptomatology may be confused with that of other phytopathogens.